\(a^{2019}+b^{2019}=a^{2020}+b^{2020}\\ \Leftrightarrow a^{2020}-a^{2019}=b^{2019}-b^{2020}=0\\ \Leftrightarrow a^{2019}\left(a-1\right)=b^{2019}\left(1-b\right)\\ \Leftrightarrow\dfrac{a^{2019}}{b^{2019}}=\dfrac{1-b}{a-1}\left(1\right)\\ a^{2020}+b^{2020}=a^{2021}+b^{2021}\\ \Leftrightarrow a^{2021}-a^{2020}=b^{2020}-b^{2021}\\ \Leftrightarrow a^{2020}\left(a-1\right)=b^{2020}\left(1-b\right)\\ \Leftrightarrow\dfrac{a^{2020}}{b^{2020}}=\dfrac{1-b}{a-1}\left(2\right)\\ \left(1\right)\left(2\right)\Leftrightarrow\dfrac{a^{2019}}{b^{2019}}=\dfrac{a^{2020}}{b^{2020}}\Leftrightarrow\dfrac{a}{b}=1\Leftrightarrow a=b\\ \Leftrightarrow2a^{2019}=2a^{2020}\\ \Leftrightarrow a=1=b\\ \Leftrightarrow P=2022-\left(1+1-1\right)^{2022}=2021\)